2010
DOI: 10.1002/cssc.201000123
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a New Type of Rechargeable Batteries Based on Hybrid Electrolytes

Abstract: Lithium ion batteries (LIBs), which have the highest energy density among all currently available rechargeable batteries, have recently been considered for use in hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), and pure electric vehicles (PEV). A major challenge in this effort is to increase the energy density of LIBs to satisfy the industrial needs of HEVs, PHEVs, and PEVs. Recently, new types of lithium-air and lithium-copper batteries that employ hybrid electrolytes have attracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 33 publications
(66 reference statements)
4
76
0
Order By: Relevance
“…The IR drop in the two electrode system is much higher than in the 3-electrode system. This has also been observed in other hybrid electrolyte systems [18][19][20][21]23]. The possible reason is that the solid electrolyte has a low lithium diffusion coefficient, which limits the rate capability of this system.…”
Section: Resultssupporting
confidence: 53%
“…The IR drop in the two electrode system is much higher than in the 3-electrode system. This has also been observed in other hybrid electrolyte systems [18][19][20][21]23]. The possible reason is that the solid electrolyte has a low lithium diffusion coefficient, which limits the rate capability of this system.…”
Section: Resultssupporting
confidence: 53%
“…Schematic representation of the proposed all-solid-state Li-air battery using Li anode, LAGP ceramic electrolyte, and an air electrode composed of SWCNTs and LAGP particles. (The yellow spheres represent Li metal, the red tetrahedral represent PO 4 , and the cyan octahedral represent GeO 6 . )…”
mentioning
confidence: 99%
“…In order to solve this problem, inorganic solid state electrolytes are introduced into the structure of Li-air batteries. [6][7][8][9][10][11] Substituting inorganic electrolyte for organic solid electrolytes can avoid side reactions caused by organic electrolytes during electrochemical process.…”
mentioning
confidence: 99%
“…22 A preliminary lithiumair fuel cell using 1 M LiClO 4 in EC&DMC/LTAP/O 2 saturated 1 M aqueous LiNO 3 solution has demonstrated that the cycle between Cu and Cu 2 O can be used to catalyze O 2 electrochemical reduction. 23 However, in the efforts to develop a rechargeable battery system using the hybrid electrolytes, 24 the lithium dendrite formation related to the organic electrolyte needs to be paid more attention.…”
mentioning
confidence: 99%